Piperacillin–tazobactam induced bicytopenia in low cumulative treatment doses. Issue 12 (30th December 2019) - Chen, Chien-Chou; Lin, Hsin-An; Hung, Yi-Jen; Chen, Jui-Hung
Abstract : We present the case of infected wet gangrene of right foot in the setting of poorly controlled type 2 diabetes in a 71-year-old woman. This patient presented with improved infection condition after intravenous piperacillin–tazobactam (PTZ) 2.25 gm every 6 hours treatment and below knee amputation surgery on day 3. However, neutropenia and thrombocytopenia developed on day 13. We consulted a haematologist and performed a series of examinations. However, no significant findings were noted thereafter. PTZ was suspected to be the most likely cause of neutropenia and thrombocytopenia and was hence terminated on day 14 (cumulative dose of PTZ: 126 g) following stabilisation of the infection condition. A transfusion was performed with two units of single donor platelets on day 14 and treated with intravenous dexamethasone 5 mg every 8 hours from day 14 to 16. Her white blood cell and platelet counts increased on day 15 and continued to recover thereafter.